Simultaneous, Dual Continuous Venovenous Haemodiafiltration as Salvage Therapy for Severe Sodium Valproate Intoxication - Aminah Hussan; Ifrah Hasan; Reem El-Hayani; Moustafa Shebl Zahra (Case Reports in Critical Care)
Sodium valproate overdose leads to CNS depression, cerebral oedema, and severe metabolic acidosis in cases of severe toxicity. Extracorporeal removal, specifically through intermittent haemodialysis, is recommended, though not always tolerated by or accessible to haemodynamically unstable patients in intensive care units. We present a case of a male in his mid-twenties presenting following a massive, intentional overdose of 13 g of sodium valproate over 7 hours, with an initial valproate blood concentration of 975 μg/ml (normal 50-100 μg/ml). He was hypoxic and severely acidotic on arrival and was given fluids and L-carnitine according to TOXBASE guidelines. This resulted in only marginal improvement to his acidosis. Once transferred to our intensive care unit, the patient was started on inotropic support followed by continuous venovenous hemofiltration (CVVHDF) at the maximum effluent rate of 60 ml/kg/hr. Due to his persisting metabolic acidosis and worsening hyperlacataemia, dual CVVHDF was started by adding another filter in series after 26 hours, increasing the maximum effluent rate to 96 ml/kg/hr. The patient remained on dual CVVHDF for 31 hours, during which his acidosis and lactate showed considerable improvement, and he was subsequently stepped down to single-filter CVVHDF for a further 20 hours until complete resolution of his acidosis. This case report recognises dual CVVHDF as a viable salvage therapy for severe sodium valproate overdose by facilitating the achievement of a higher effluent flow rate compared to what can be accomplished with single-filter CVVHDF.